(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Frictional resistance at the bracket-archwire interface is a critical determinant of force delivery during sliding mechanics. Bracket design, slot material, ligation method, and archwire alloy may modify static and kinetic friction, thereby influencing clinical efficiency during alignment and space closure. Methods This in vitro experimental study compared frictional resistance among three 0.022-inch slot bracket systems: conventional stainless steel brackets with elastomeric ligation, passive selfligating stainless steel brackets, and polycrystalline ceramic brackets with elastomeric ligation. Three archwire materials were tested: 0.019 x 0.025-inch stainless steel, nickel-titanium, and beta-titanium. Ninety bracket-archwire assemblies were prepared, with 10 specimens per bracket-wire combination. Testing was performed using a universal testing machine at a crosshead speed of 5 mm/min under artificial saliva lubrication at 37 degrees C. Static frictional resistance and kinetic frictional resistance were recorded in Newtons. Data were analysed using two-way ANOVA and Tukey post hoc tests. Results Mean static friction differed significantly by bracket type and wire material (p<0.001). Self-ligating brackets showed the lowest overall static friction (1.42 +/- 0.32 N), followed by conventional stainless steel brackets (2.37 +/- 0.46 N), whereas ceramic brackets showed the highest values (3.29 +/- 0.58 N). Stainless steel archwires produced the lowest mean static friction (1.67 +/- 0.48 N), nickel-titanium produced intermediate values (2.33 +/- 0.67 N), and beta-titanium produced the highest values (3.08 +/- 0.79 N). The highest friction was observed with ceramic brackets and beta-titanium wires (4.12 +/- 0.39 N), while the lowest was recorded with self-ligating brackets and stainless steel wires (0.98 +/- 0.18 N). Conclusion: Frictional resistance was significantly influenced by both bracket system and archwire material. Passive self-ligating brackets combined with stainless steel archwires offered the most favourable low-friction combination, whereas ceramic brackets with beta-titanium archwires generated the highest resistance. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S276-S282